EL-CAFE BENGKULU SALES DATA PROCESSING SYSTEM - Jumadi; Kirman (Media Inovasi Pendidikan dan Publikasi, 2023)
El-café Bengkulu is a company engaged in the culinary field, which so far sells its products using manual recording, which has the potential for huge errors, such as errors in recording sales transactions. The purpose of this research is to be able to maximize the sales transaction revenue process for Bengkulu E-Cafe products, so that the losses experienced can be minimized. This research succeeded in designing and building the El-Café Bengkulu Sales Data Processing System, so that the transaction process for food and beverage sales can be well controlled. Checking data on the results of food and beverage sales can be done easily and does not require much time. calculated automatically, so the calculation process will not be wrong. Suggestions and recommendations that can be given are that the El-Café Bengkulu Sales Data Processing System needs to be developed and can be accessed on-line so that the sales process can be carried out at home or other places so that it can be controlled regularly. This can be done using other programming languages